PENILAIAN POTENSI EKOWISATA DI SITU TONJONG KABUPATEN BOGOR - Aini Syarah; Aditya Sugih Setiawan; Rima Pratiwi Batubara (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Bogor Regency is one of the leading destinations in the West Java region. Bogor Regency has beauty that is famous for its culture and biodiversity. This is a valuable resource for this region for the growth of the welfare of its people. The diverse tourism potential includes natural, gastronomic and artifact tourism potential as well as special interest tourism. There are natural tourism potentials in Bogor district that can be developed, such as the Mount Pancar pine forest, Cilember Waterfall, Bodogol Javanese eagle rookery, Gunung Mas tea plantation and Situ Tonjong. The research method used is qualitative research. Data collection techniques were carried out using observation, in-depth interviews as well as potential assessments and literature studies. The variables used in this ecotourism potential assessment research refer to natural phenomena, flora, fauna and green open spaces. The results of identifying ecotourism potential in the Situ Tonjong area are in the form of natural phenomena, namely situ. Meanwhile, in the flora there is ecotourism potential in the form of mahogany trees, teak trees, coconut trees, jackfruit trees, petai trees and water hyacinth. In contrast, the ecotourism potential of the existing fauna consists of goldfish, tilapia fish, tilapia fish and gourami fish. The final ecotourism potential in the Situ Tonjong area is in the form of a green open space area.